CD28 and CTLA4 polymorphisms associated with ankylosing spondylitis: a study in the context of HLA-B27 - Kuang-Hui Yu; Gem Huai-Chueh Wu; Chia-Ju Yang; Wei-Tzu Lin; Fang-Ping Hsu; Ding-Ping Chen (BMC Immunology)
Abstract Background The human leukocyte antigen (HLA)-B27 gene is highly associated with ankylosing spondylitis (AS). However, not everyone who carries the HLA-B27 antigen develops AS, indicating that factors beyond the HLA-B27 gene contribute to the disease’s onset. AS is an autoimmune disease in which co-stimulatory systems have been widely explored. Therefore, we aimed to analyze the association between single-nucleotide polymorphisms (SNPs) in co-stimulatory/inhibitory molecules and AS to identify other key factors involved in developing the disease. Results This study recruited 32 patients with AS and 32 controls. DNA was extracted from whole blood, and PCR amplification was performed to target the promoter regions of the CTLA4, CD28, and PDCD1 genes. Chi-square and Fisher’s exact tests were used under various genetic models to assess differences in genotype and allele distribution between cases and controls. The results showed that rs201801072 of the CD28 gene (TT + CT vs. CC, p = 0.001) and rs11571319 of the CTLA4 gene were associated with AS (GG vs. AG + AA, p = 0.001). Logistic regression analysis showed that rs201801072 (CD28) and rs11571319 (CTLA4) were independently associated with AS. A significant positive interaction was observed between these SNPs and HLA-B27 positivity, further increasing the risk of AS (T-allele: OR = 6.15; G-allele: OR = 13.30, both p < 0.001). HLA-B27 carriers exhibited an extremely high risk of AS (OR = 65.0, p = 1.19E-06). Conclusions The elevated frequencies of specific alleles in AS patients compared to controls highlight the potential involvement of these SNPs as key factors in the pathogenesis of AS, offering new insights into the genetic mechanisms underlying the disease.